Efeitos de uma ação formativa sobre o reconhecimento de sinais precoces do autismo para professores - Fanchioni, Isabela Martins (Universidade Federal de São Carlos, 2026)
Autism Spectrum Disorder (ASD) is characterized by impairments in communication and social interaction, and restricted and repetitive patterns of behavior. Characteristic signs of ASD are present from the child's first months, and their recognition constitutes a protective factor against possible worsening of the characteristics, as well as the possibility of an improvement in development and an increase in adaptive, verbal, and social behaviors. Teachers point to difficulty in recognizing these signs at school due to a lack of knowledge on the subject. Therefore, the objective of this work was to create, evaluate and implement an remote expository in-person training action on the identification of early signs and characteristics of ASD in Early Childhood Education teachers. The research used a single-subject quasi-experimental design with pre- and post-tests and follow-up. The procedures used were an initial assessment (pre-test), training, followed by a final assessment (post-test), at the end of the three stages, and after two months was applied the follow-up. The participants were three teachers. The results indicated that the participants began to recognize the early signs and definitions of ASD. This result corroborates previous findings in the literature that also indicated that training, even of short duration, can produce advances in teaching knowledge about ASD.
Efects of a training action on the identification of early signs and characteristics of ASD in early childhood education for teachers
Keywords: Educação especial; TEA; Sinais precoces; Educação infantil; Escola; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL; 3. Saúde e Bem-Estar